A New Measure for Detecting Influential DMUs in DEA. (16th October 2014) - Acarlar, Irmak; Kınacı, Harun; Najjari, Vadoud
Abstract : We discuss about influential DMUs and also we review some related studies in the literature. Then we propose a new method to detect influential DMUs, which is based on Euclidean distance and omitting the efficient DMUs by using single case deletion. Our method will be explained with an empirical example.